ROLE OF ATYPICAL CHEMOKINE RECEPTOR 2 IN PERIVASCULAR ADIPOSE TISSUE INFLAMMATION IN ANGIOTENSIN II DEPENDENT HYPERTENSION. (April 2021) - Mikolajczyk, Tomasz; Skiba, Dominik; Vidler, Francesca; Love, Samantha; Justo-Junior, Amauri; Nosalski, Ryszard; Graham, Delyth; Maffia, Pasquale; Graham, Gerard; Guzik, Tomasz
Abstract : Objective: Hypertension (HT) is associated with perivascular adipose tissue (PVAT) inflammation in which chemokines play a crucial role. Atypical chemokine receptor 2 (ACKR2) is essential for CC-chemokine ligand binding and their degradation resulting in regulation of inflammation. We hypothesized that ACKR2 is important for immune cell recruitment into PVAT. Design and method: Using flow cytometry we analysed the numbers of leukocytes infiltrating PVAT in ACKR2-/- mice and WT (wild-type, C57BL/6J) infused for 14 days with Ang II (angiotensin II, 490ng/min/kg). Results: Chronic infusion of Ang II caused increased of leukocyte (CD45+) content in PVAT in both WT and ACKR2-/- mice. This increase was particularly evident for T cell subsets in WT but not in ACKR2-/-. However the number of macrophages (F4/80+CD11b+) was increased in both groups. Interestingly, ACKR2-/- revealed decreased T cell number infiltrating PVAT upon Ang II infusion in comparison to WT. Hypertension was associated with increased CCR1, CCR2 and CCR3 expression in PVAT in both WT and ACKR2-/-. However, ACKR2-/- revealed higher expression of CCR1 and CCR2 but not CCR3 in comparison to WT. Interestingly, increased expression of CCR5 in PVAT upon Ang II infusion in WT was not observed in ACKR2-/-. Hypertension resulted in increased RANTES level in aorta and PVAT to the same extent in both WT and ACKR2-/-. However, MCP-1, MIP-1 alpha and MIP-1 beta level was higher in ACKR2-/- aorta than in WT aorta upon Ang II infusion. ACKR2 expression was lower in PVAT than in aorta. Interestingly, Ang II administration decreased the expression of ACKR2 in aorta but increased ACKR2 level in thoracic PVAT. RNAscope analysis revealed ACKR2 expression in vascular smooth muscle cells (VSMC). Vessels isolated from ACKR2-/- were protected from vascular dysfunction and revealed reduced ROS production in comparison to WT upon Ang II administration. ACKR2-/- mice developed similar extent of blood pressure increase as WT in hypertension. Conclusions: In hypertension, ACKR2-/- is associated with decreased T cell content and reduced CCR5 expression in PVAT. This is accompanied by improved vascular function and diminished ROS production, independently of blood pressure regulation.